Correction Of Anemia with Red Blood in Patients with Liver Circulosis - Ibragimov Nematjon Komiljonovich; Khushbokov Bakhodir Azamatovich; Qaxxorov Nodirjon Adxamjon ogli; Rixsiboyev Avaz Shavkatovich (Zien Journals, 2022)
Anemia of various etiologies is a common complication of chronic liver disease. Causes of anemia include acute or chronic gastrointestinal bleeding and secondary hypersplenism to portal hypertension. Severe hepatocellular disease is prone to bleeding due to lack of blood clotting factors synthesized by hepatocytes and / or impaired blood clotting caused by thrombocytopenia. After the development of hepatitis, aplastic anemia characterized by pancytopenia and hypocellular bone marrow may occur. Its presentation includes progressive anemia and hemorrhagic manifestations. Hematological complications of complex treatment of chronic viral hepatitis include clinically significant anemia resulting from treatment with ribavirin and / or interferon. This article discusses, data on the correction of anemia when bleeding from the esophagus in patients with cirrhosis of the liver.
Keywords: Anemia; liver disease; liver failure; anemia